The Relationship Between Sensory Disability Status and Contraceptive Use Among Women Aged 15- 49 Years Old In South Africa - Sifora, Kutlwano Katlego Kimberly (University of the Witwatersrand, Johannesburg, 2024)
Background: Studies suggest that disability significantly hinders access to reproductive health services, particularly family planning, in low- and middle-income countries. Women with disabilities have a low contraceptive use rate, leading to increased risks of unintended pregnancies and health complications. This study examined the relationship between sensory disability status and contraceptive use in South Africa. A sensory disability is a condition that affects one or more of the body's sensory functions like sight, hearing, touch, taste, or smell. In this study, sensory disabilities focused on hearing and visual impairments. Methods: The study employed a cross-sectional design using the 2016 South Africa Demographic and Health Survey. The study focused on women of reproductive age (15–49 years old) in South Africa, who were sexually active and provided information on both their contraceptive use and sensory disability status. The outcome variable of this study was contraceptive use, and the main independent variable was sensory disability status. The control variables included demographic characteristics namely age, race, marital status, province, and place of residence, as well as socioeconomic characteristics such as employment status, wealth status, education, family planning messages, and contraceptive knowledge. The analysis was conducted using Stata 17.0 on a weighted sample of 6 683 sexually active women aged 15–49 years old who answered questions on contraceptive use. The data analysis was done in three phases. For the first phase, cross-tabulations and chi-square analysis were used to demonstrate the levels of contraceptive use as well as all characteristics of women. For the second phase, bivariate binary logistic regression models were used to determine the relationship between each of the independent variables and the outcome variable of contraceptive use. Lastly, for the third phase, a stepwise multivariate binary logistic regression was utilised to determine the relationship between sensory disability status and contraceptive use among women aged 15– 49 years old in South Africa. Results: Among South African women of reproductive age, 55.4% were using contraceptives. Women with sensory disabilities were shown to have lower odds of using contraceptives than those without sensory disabilities, even after adjusting for all other variables [OR: 0.78, CI: 0.63873 - 0.95227]. Significant associations with contraceptive use were observed for factors xi including age, race, marital status, education and province. Compared to women aged 15–24, women aged 35–39 had a much lower likelihood of using contraceptives. [OR: 0.46, CI: 0.38150 - 0.55364]. Women from races other than black were also observed to have lower odds for contraceptive use compared to black women [OR: 0.75, CI: 0.61098 - 0.92237]. Conversely, married women were significantly more likely to use contraceptives than women who were never married [OR: 1.23, CI: 1.05328 - 1.42899]. Additionally, women with secondary [OR: 1.98, CI: 1.28089 - 3.07512] or higher education [OR: 2.40, CI: 1.49931 - 3.83750] exhibited a significantly higher likelihood of contraceptive usage compared to those lacking formal education. Women residing in Western Cape [OR: 1.83, CI: 1.29743 - 2.57637], Eastern Cape [OR: 1.66, CI: 1.27747 - 2.15886], Northern Cape [OR: 1.61, CI: 1.18574 - 2.19087], KwaZulu Natal [OR: 1.51, CI: 1.17797 - 1.92456], North West [OR: 1.43, CI: 1.01266 - 2.01228], and Mpumalanga [OR: 1.50, CI: .15808 - 1.93439] were found to have a higher likelihood of using contraceptives compared to women residing in Limpopo. Conclusions: Low contraceptive use among women with sensory disabilities in South Africa highlights the need for inclusive reproductive health services, addressing communication, information access, and societal attitudes to ensure informed decisions.
A research report Submitted in fulfillment of the requirements for a Masters Degree (MA) in the field of Demography and Population Studies, In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: Contraceptive use; Sensory Disability Status; South Africa; SDG-5: Gender equality; SDG-3: Good health and well-being